Perancangan Sistem Informasi Desa Berbasis Web Di Desa Bolora Kecamatan Wewewa Tengah - Marselinus Umbu Zogar; Pingky Alfa Ray Leo Lede; Desy Asnath Sitaniapessy (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The rapid development of information technology today demands that we master and utilize it effectively. One of the rapidly evolving information technologies is the website. Websites can provide information quickly and accurately. In the context of village governance, the current situation is improving with the presence of village fund allocations from the central government aimed at advancing villages. Information technology can assist village officials in enhancing services to village residents, making information access easier, promoting community business products, showcasing village potentials, population data, and land area. Therefore, a Web-Based Village Information System has been developed in Bolora Village using the waterfall model. This village information system is expected to facilitate faster, more accurate, and efficient services to residents. Additionally, residents can easily and quickly obtain information through the village website.